Latest trends and their adoptions in electrical power systems – an industrial perspective - Koti Reddy, Butukuri; Srirajvarun Reddy, Bhanur; Prakash, Palavarapu; Vamshy, Dongari; Ram Kishore Kumar Reddy, Penubaka; M. Alhaider, Mohammed (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
Electricity is a vital part in every day’s life and is one of the greatest gifts given by science to the mankind. It has provided all the comfort to the human beings right from lighting to large machines through computers and amusement equipment. Electrical power system (EPS) is moving fast into new horizons and making the entire world dynamic just like the speed of electron. In this paper, the latest trends that are happening globally in electrical power systems are highlighted. The major changes that are taking place in all applicable fields such renewable energy, especially photovoltaics (PV), smart grids (SG), ulta high voltage (UHV) transmission, distributed generation, micro grids, de-regulation and e-mobility are reviewed for updating all the stake holders of it. Also, the adoption of latest technologies such as internet of things (IoT) and artificial intelligence (AI) are briefly mentioned.